2010
DOI: 10.5897/ajb09.1368
|View full text |Cite
|
Sign up to set email alerts
|

In silico cloning and bioinformatic analysis of PEPCK gene in Fusarium oxysporum

Abstract: Phosphoenolpyruvate carboxykinase (PEPCK), a critical gluconeogenic enzyme, catalyzes the first committed step in the diversion of tricarboxylic acid cycle intermediates toward gluconeogenesis. According to the relative conservation of homologous gene, a bioinformatics strategy was applied to clone Fusarium oxysporum phosphoenolpyruvate carboxykinase gene (PEPCK) by blasting search of EST database with homologous gene cDNA of Neurospora crassa and identified. Some characters of the PEPCK that were analyzed and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 7 publications
0
3
0
Order By: Relevance
“…The derived amino acid sequence encoded by CaPEPCK1 is 662 residues in length and is predicted to have a theoretical isoelectric point (pI) of 6.55 and a molecular weight of 73.2 kDa, as determined using the Expasy Compute pI/Mw tool (http://web.expasy.org/ compute_pi/). Domain search analysis of CaPEPCK1 using the SMART server (http://smart.embl-heidelberg.de/) identified a PEPCK_ATP domain at amino acid position 138-609 that is known to be conserved in bacteria, fungi, insects, and plants (Friedlander et al 1996;Bahrami et al 2001;Lee et al 2002;Li et al 2010). Sequence comparison analysis using the BLASTx server (http://blast.ncbi.nlm.…”
Section: Resultsmentioning
confidence: 99%
“…The derived amino acid sequence encoded by CaPEPCK1 is 662 residues in length and is predicted to have a theoretical isoelectric point (pI) of 6.55 and a molecular weight of 73.2 kDa, as determined using the Expasy Compute pI/Mw tool (http://web.expasy.org/ compute_pi/). Domain search analysis of CaPEPCK1 using the SMART server (http://smart.embl-heidelberg.de/) identified a PEPCK_ATP domain at amino acid position 138-609 that is known to be conserved in bacteria, fungi, insects, and plants (Friedlander et al 1996;Bahrami et al 2001;Lee et al 2002;Li et al 2010). Sequence comparison analysis using the BLASTx server (http://blast.ncbi.nlm.…”
Section: Resultsmentioning
confidence: 99%
“…With more and more EST and genome sequencing data were reported, it would become possible and feasible to isolate and identify the functional genes by in silico cloning. Many successful examples strongly support the fact that in silico cloning is absolutely a feasible tool for gene cloning and presents some advantages, compared to the traditional methods [8]. In this study, the full cDNA of Raphanus sativu WUS was obtained primarily by searching and splicing the EST sequences.…”
Section: Disscusionmentioning
confidence: 94%
“…Study by Khandaker et al [25] showed the similar decreasing trend in fruit physical properties, which continuous decrease in weight an diameter of the fruit as days increase. The physical properties evolution directly was effecting the value of the stiffness of the tomatoes [19], [26].…”
Section: Physical Properties Of Tomatomentioning
confidence: 99%